Workload and Psychological Well-Being among ASN Teachers at SMAN 1 Solok Selatan - Cindy Claudia; Suci Rahman Nio (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Teachers’ psychological well-being is essential for maintaining effective and sustainable professional functioning; however, increasing demands within school environments may create excessive workloads that undermine their well-being. This study examined the relationship between workload and psychological well-being among state civil apparatus (ASN) teachers at SMAN 1 Solok Selatan. A quantitative correlational design was employed, involving 39 ASN teachers selected through saturated sampling. Data were collected using a 24-item workload scale and the 35-item Ryff Psychological Well-Being Scale and analyzed using Pearson’s product–moment correlation. The results demonstrated a statistically significant, moderate negative relationship between workload and psychological well-being (r = −0.445, p = .005), indicating that higher workload was associated with lower psychological well-being. The squared correlation coefficient (R² = .198) indicated that workload shared 19.8% of the variance in psychological well-being, while the remaining variance was not accounted for by workload in the bivariate model. These findings underscore the importance of managing teachers’ workload to protect their psychological well-being and sustain their professional functioning. The study provides practical implications for schools and educational stakeholders seeking to establish more balanced workload arrangements and supportive work environments. Further research should investigate additional individual, organizational, and occupational factors associated with teachers’ psychological well-being. Keywords: ASN Teachers; Occupational Well-Being; Psychological Well-Being; Teacher Workload; Secondary Education